On Value Distribution of Differential Polynomials of Meromorphic Functions - Banerjee, Dibyendu; Ghosh, Ishita (Journal of Nepal Mathematical Society, 2026)
In a recent paper, Fan et. al. showed that for a non-homogeneous differential polynomial formed with a non-constant meromorphic function f, <strong class="Yjhzub" data-sfc-root="ep" data-sfc-cb="" data-complete="true" data-copy-service-computed-style="font-family: "Google Sans", Arial, sans-serif; font-size: 16px; font-weight: 600; margin: 0px; text-decoration: none; border-bottom: 0px rgb(0, 29, 53);">Θ(a, <kbd>φ(f)</kbd><strong class="Yjhzub" data-sfc-root="ep" data-sfc-cb="" data-complete="true" data-copy-service-computed-style="font-family: "Google Sans", Arial, sans-serif; font-size: 16px; font-weight: 600; margin: 0px; text-decoration: none; border-bottom: 0px rgb(0, 29, 53);"><kbd>)</kbd> is bounded above by 1. In this paper, we extend two results for differential polynomials formed with two meromorphic functions.